Description of Epistylis riograndensis n.sp. (Ciliophora: Peritrichia) found in an artificial lake in Southern Brazil - Utz, Laura R. P.; Farias, Ana Carolina Silva Rodrigues; Freitas, Eduarda Correa; Araújo, Gabriella Oliveira De (Zootaxa, 2014)
Epistylis riograndensis n. sp., a freshwater peritrich hosting symbiotic algae in its cytoplasm, was collected from an artificial lake, in a Botanical garden in Southern Brazil. Its detailed morphology was investigated using live and silver-stained specimens. The colonial sessile E. riograndensis has elongate zooids measuring, on average, 162 μm in length and 45 μm in width. A single contractile vacuole located near the infundibulum and a C-shaped macronucleus located transversely in the adoral half of the cell were also observed. The oral infraciliature revealed in silver-stained specimens was typical of peritrich ciliates. Three infundibular polykineties consisting of 3 rows of kinetosomes were observed. Molecular analyses of 18s rDNA placed E. riograndensis among other Epistylis species in the Order Vorticellida.